Global Governance, COVID 19 & Resesi di Negara ASEAN - Tedy Chandra; Stefanny Valencia Halim; Fikri Fadilah (FISIP Universitas Tanjungpura, 2022)
This paper aims to explain how the alleviation of the recession that